UJI KINERJA DAN ANALISIS EKONOMI MESIN PENEPUNG BIJI JAGUNG (Studi Kasus di Desa Cikawung, Kecamatan Ciparay, Kabupaten Bandung) - Wahyu K Sugandi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2019)
Animal feed is substantial in the livestock industry. There is a stock breeder in Cikawung, Ciparay sub-district for enlarging broiler chicken. But the breeder has constraints with the high prices of animal feed. Otherwise, high amount of corn is an opportunity for breeders to save operational cost for animal feed. The purpose of this research was to test the performance and economic analysis on corn milling machine whose have been developed by Agricultural Machinery Laboratory of FTIP Unpad and applied to breeder. The method used in the research is descriptive analysis by measuring and calculating on performance and economic feasibility of machine. The result of machine performance test showed the theoretical capacity for 54,53 kg/hour, actual capacity is 29,73 kg/hour, machine efficiency is 54,52%, actual power requirement of machine without load and with load are 3,12 HP and 4, 37 HP, engine fuel consumption with no-load and loads of 0,96 liters/hour and 1,41 liters/hour, thermal efficiency ranges from 21-28%, shrinkage losses 2,65%, yield 97,35%, engine noise level of 83 dB, and with load of 86,93 dB, and engine vibration rate exceeding 4,5 mm/s (not allowed). The results of economic analysis showed that BEP achieved after the machine produces 48.657,83 kg corn flour. The corn milling machine fulfilled the criteria of economic feasibility indicated by positive NPV value, IRR of 25,67%, B/C Ratio of 1,012 and PBP for 2,75 years.